Elaboração de uma unidade de ensino para investigação da tensão de corte do LED - Santos, Robson Domingos da Cruz (2020)
The teaching of physics in high school should allow the construction of knowledge necessary for understanding the contemporary world. Here is a sequence, based on the significant learning of David Ausubel and previous organizers, that allows students to get closer to new technologies, and not only that, it allows them to have a sense of physics behind these technologies, and also to know how to identify. The sequence was divided into two moments, in the first application, an organizer previously implemented in Algodoo, using the steps of the PODS cycle (Prediction, Observation, Demonstration and Synthesis), which aimed at the concept of students' cognitive structure management, used for: learning the main concept. In the second moment, a demonstration class was developed with the Arduino, using a simple circuit that can modify the current flow that passes through the LED, obtaining a voltage versus current graph to determine the cutoff voltage. During a demonstration, comments were required on the formation of potential barriers, band theory, semiconductors and PN junction. It concludes that although this activity illustrates the practical application of these concepts, these procedures have a deeper individual approach for the adequate assimilation of their meanings.